2009
DOI: 10.1002/cncy.20042
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the routine screening performance of cytotechnologists over time

Abstract: BACKGROUND: Documenting the performance of gynecologic screening in actual practice settings is difficult to achieve. In the current study, the screening performance of 11 individual cytotechnologists as well as that of the overall laboratory over 2 consecutive time periods was examined using the rapid prescreening (RPS) method. METHODS: RPS was performed by all cytotechnologists in a single laboratory over 2 separate 8-month periods. The sensitivity of screening for individual and groups of cytotechnologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…As shown in various studies, it is possible to use abnormal cases identified both by rapid prescreening and by routine screening to monitor the performance of professionals in the daily routine of cytology laboratories. 6,9,20,[22][23][24][25] Nonetheless, it is only in Canada and the United Kingdom that this method is being routinely used. 4,25,26 Finally, the high rates of false-negatives constitute one of the principal problems faced by cytology laboratories.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in various studies, it is possible to use abnormal cases identified both by rapid prescreening and by routine screening to monitor the performance of professionals in the daily routine of cytology laboratories. 6,9,20,[22][23][24][25] Nonetheless, it is only in Canada and the United Kingdom that this method is being routinely used. 4,25,26 Finally, the high rates of false-negatives constitute one of the principal problems faced by cytology laboratories.…”
mentioning
confidence: 99%
“…6,9,20,[22][23][24][25] Nonetheless, it is only in Canada and the United Kingdom that this method is being routinely used. 4,25,26 Finally, the high rates of false-negatives constitute one of the principal problems faced by cytology laboratories. Of the internal quality control methods currently available, 10% random review is the least effective for detecting false-negative results at routine screening.…”
mentioning
confidence: 99%
“…In addition, it has recently been shown that long-term use of RPS significantly improves the estimated sensitivity of a subset of individual CTs in routine screening, presumably by providing constant, accurate, real-time feedback, improving both the accuracy and precision of the laboratory [12]. Previous studies have shown that the effectiveness of RPS is dependent on the time spent screening (the longer one is allowed to examine a case, the higher the estimated sensitivity [1]), and the technique used (the step technique being more sensitive than other techniques, at least in conventional smears [1]).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Using these surrogates, the maximum workload for cytotechnologists can be estimated so they have the best chance of achieving near-100% sensitivity. That workload is 30 slides/d for manual screening of conventional [8][9] and SurePath (BD Biosciences, Franklin Lakes, New Jersey) cases, 10 and an ECA-adjusted workload of 7 cases/d (or 70 cases/d for a laboratory with an ECA rate of 10% where 1 slide is counted as 1 slide) for screening with the ThinPrep Imaging System (Cytyc Corporation, Boxborough, Massachusetts). 5,11 Unfortunately, those workloads are less than the workloads currently being employed in some, if not many, cytology laboratories.…”
Section: Gynecologic Cytology: How Fast?mentioning
confidence: 99%